2017
DOI: 10.1016/j.jalz.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver reactions to clinical amyloid imaging

Abstract: INTRODUCTION Amyloid imaging is a tool that has recently become available to dementia specialists evaluating patients with possible Alzheimer’s disease. Studies have assessed the impact of amyloid imaging on diagnostic and treatment decisions, but patient and family perspectives have received less attention. METHODS To examine how amyloid imaging affects the diagnostic experience for patients and families, we interviewed members of 26 patient-caregiver dyads with whom a neurologist discussed the option of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 43 publications
(41 reference statements)
9
63
0
Order By: Relevance
“…In particular, the participants’ ability to voice their concerns and have a medical justification to their forgetfulness was comforting. One recent study also suggested that receiving diagnostic information about AD can be associated with feeling of relief [44]. Indeed, a traditional role of diagnosis is to relieve patients from the weight of carrying the burden of symptoms on their own [45].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the participants’ ability to voice their concerns and have a medical justification to their forgetfulness was comforting. One recent study also suggested that receiving diagnostic information about AD can be associated with feeling of relief [44]. Indeed, a traditional role of diagnosis is to relieve patients from the weight of carrying the burden of symptoms on their own [45].…”
Section: Discussionmentioning
confidence: 99%
“…A key perspective that has been relatively underrepresented until now is the perspective of the patients themselves [ 13 15 ]. One study explored the views of patients and caregivers on amyloid PET imaging [ 16 ]. In that study, the views of the 23 caregivers outnumbered the views of the 9 included patients (7 patients with an amyloid-positive PET scan, 2 with an amyloid-negative PET scan) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study explored the views of patients and caregivers on amyloid PET imaging [ 16 ]. In that study, the views of the 23 caregivers outnumbered the views of the 9 included patients (7 patients with an amyloid-positive PET scan, 2 with an amyloid-negative PET scan) [ 16 ]. In addition, the diagnosis in the patient population ( n = 26) was heterogeneous (e.g., mild cognitive impairment [MCI], atypical presentation of AD dementia, young-onset cognitive impairment) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the inadequacy of current treatments to alleviate the symptoms of the disease. Also, the difficulty in developing novel interventions to detect [1–57], delay [58–69], or halt disease progression continues to be an important hurdle. The well‐recognized public health and economic imperative [70–83] posed by the disease continues to be an important motivator to communicate new knowledge across multiple disciplines that will help increase the likelihood of unlocking the complexity of neurodegeneration [84–90] associated with many dementing illnesses.…”
mentioning
confidence: 99%